2010
DOI: 10.1111/j.1365-3083.2010.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mycobacterium smegmatis Expressing an ESAT6‐CFP10 Fusion Protein Induces Anti‐Mycobacterial Immune Responses and Protects Against Mycobacterium tuberculosis Challenge in Mice

Abstract: The currently used vaccine against tuberculosis, Bacille Calmette‐Guérin (BCG), has variable efficacy, so new vaccine development is crucial. In this study, we evaluated a recombinant vaccine prepared from non‐pathogenic Mycobacterium smegmatis (rMS) that expresses a fusion of early secreted antigenic target 6‐kDa antigen (ESAT6) and culture filtrate protein 10 (CFP10). C57BL/6 mice were immunized with the rMS expressing the ESAT6‐CFP10 fusion protein (rM.S‐e6c10) or with BCG. The mice in the rM.S‐e6c10 group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Immunized mice with this rMS showed induced protection against Mtb challenge and dramatic decrease of bacteria loads in lung. 18 We also demonstrated that the rMS strain expressing the fusion protein of heparin-binding hemagglutinin and human IL-12 (HBHA-IL-12) enhanced immunogenicity and improved Th1-type responses against TB, with the protective effects equivalent to that of the conventional BCG vaccine in mice. 19 Moreover, this rMS also decreased the bacterial load and pathological damage in lung of Mtb-infected mice.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Immunized mice with this rMS showed induced protection against Mtb challenge and dramatic decrease of bacteria loads in lung. 18 We also demonstrated that the rMS strain expressing the fusion protein of heparin-binding hemagglutinin and human IL-12 (HBHA-IL-12) enhanced immunogenicity and improved Th1-type responses against TB, with the protective effects equivalent to that of the conventional BCG vaccine in mice. 19 Moreover, this rMS also decreased the bacterial load and pathological damage in lung of Mtb-infected mice.…”
mentioning
confidence: 94%
“…plasmid was transformed into MS by electroporation, and the transformed recombinant MS bacteria were selected on solid 7H10 agar containing hygromycin (50 μg/ml, Sigma-Aldrich) for 3 d. 18 After selection, the bacteria were harvested, boiled in loading buffer and analyzed by western blotting using monoclonal antibody against ESAT6 and polyclonal antibody against Ag85B (Santa Cruz Biotechnology). Positive rMS strain after screening was designated AE-rMS.…”
Section: Construction Of Ae-rmsmentioning
confidence: 99%
“…Among them, CFP10 and ESAT6 are immunodominant antigens encoded by region of difference-1 (RD1) that are present in virulent strains of Mtb and Mycobacterium bovis; however, these antigens are absent in BCG (24)(25)(26). Loss of RD1 was hypothesized to be the contributing factor for the attenuation of BCG (27,28); therefore, RD1-encoded CFP10 and ESAT6 have often been selected as potential antigen candidates in the development of novel anti-TB vaccines (19,(29)(30)(31)(32). In addition to CFP10 and ESAT6, Ag85A and Ag85B have also been widely employed in anti-TB vaccine development (32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a delivery vector, proper Mtb antigens used for vaccine development are also key factor for effectiveness of a vaccine candidate (16,17). Previously, a number of microbial antigens of Mtb were tested as TB vaccine candidates, including 10-kDa culture filtrate protein (CFP10), 6-kDa early-secreted antigenic target (ESAT6), the 30-32 kDa family of three proteins [antigen 85 (Ag85)A, Ag85B and Ag85C], the Mtb protein 64 (MPT64) and TB10.4 (a protein of 96 amino acids with a theoretical molecular mass of 10.4 kDa) (18)(19)(20)(21)(22)(23). Among them, CFP10 and ESAT6 are immunodominant antigens encoded by region of difference-1 (RD1) that are present in virulent strains of Mtb and Mycobacterium bovis; however, these antigens are absent in BCG (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Among these antigens, CFP10 (ESXB) and ESAT6 (ESXA) proteins belong to ESAT6 family ( Table 1). Both of these proteins were first identified from the short term culture filtrate of M. tuberculosis [37], and preferentially induce positive responses with cells from humans and animals infected with M. tuberculosis and Citation [70][71][72]. However, it will not be possible to use the same set of proteins for diagnosis as well as vaccination because it will jeopardize their diagnostic value to detect infection with M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%